Masjid Syuhada Yogyakarta's Development in Zakat, Infaq, and Shadaqah from 2015 to 2019 - Mayang, Sekar (ZISWAF ASFA, 2023)
Yogyakarta is an area with a predominantly Muslim population, making mosques central to religious, social, and economic activities. The Syuhada Mosque in Yogyakarta was selected as the focus of this research to examine the development of zakat, infaq, and shadaqah management through the LAZIS Syuhada institution from 2015 to 2019. This study employs a qualitative method, utilizing data collection techniques such as observation, interviews, and direct documentation with LAZIS Syuhada managers. The aim of the study is to understand the mechanisms of collection, utilization, and distribution of zakat, infaq, and shadaqah funds, as well as their impact on the economic and social empowerment of the surrounding community. The findings indicate that LAZIS Syuhada effectively manages funds in a transparent and organized manner, distributing assistance to eight categories of beneficiaries (asnaf) and implementing various empowerment programs. These programs include Mahasantri scholarships, health assistance for the underprivileged, and initiatives for women's economic empowerment. The presence of LAZIS Syuhada enhances the role of mosques as centers for community empowerment and contributes to improving the welfare of the community in a sustainable way. This study makes a significant contribution to the development of zakat, infaq, and shadaqah management within the mosque environment in Yogyakarta.